Illegal Downloading and Copyright Infringement: An Ethical Problem in Information Technology - Desra Triyunsari (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2024)
Copyright is an exclusive right automatically granted to creators upon the realization of their work in a tangible form, in accordance with declarative legal principles and within the scope of existing legislation. Copyright infringement causes significant harm to creators, particularly through economic loss. Therefore, legal protection of copyright must be enforced effectively. Cinematographic works, such as films, are among the creative works protected by copyright law. However, in practice, digital piracy is prevalent, with many individuals illegally downloading or reproducing original films. The development of information technology has brought substantial benefits but also harmful effects, including the widespread occurrence of digital piracy. The lack of public awareness and understanding regarding copyright law enforcement contributes to persistent violations, including illegal film downloading. This study examines the legal and ethical implications of digital piracy and explores the enforcement of copyright law to address the issue of illegal downloading in Indonesia.